Modeling of the Development of a Group of Gas Deposits While Accounting for Their Liquidation - Khachaturov, V. R.; Solomatin, A. N.; Skiba, A. K. (Automation and remote control, 2018)
We consider a mathematical model of a group of gas deposits and software tools that allow to devise long-term strategies for the development of a group of deposits based on the joint use of simulation modeling, discrete and multicriteria optimization. We envisage the possibility of liquidation of deposits, and we study the model of a gas deposit’s operation taking into account the creation of a special fund for financing liquidation works.